PENINGKATAN HASIL BELAJAR MATEMATIKA SISWA DENGAN PENDEKATAN PEMBELAJARAN KONTEKSTUAL MELALUI PENERAPAN KOMBINASI METODE CERAMAH, DEMONSTRASI DAN LATIHAN DI KELAS IIIA SD NEGERI 81 BENGKULU SELATAN - Suminto Suminto (PAKAR Pendidikan, 2015)
Efforts to improve the quality of mathematics learning process is still being done to achieve the goals of mathematics education. However mathematics until now was difficult by many primary school students, one indicator is the low student learning outcomes. This study aimed to find out how the application of a combination of lectures, demonstrations and exercises with contextual learning approach to improving student learning outcomes in mathematics Elementary School Class IIIA 81 South Bengkulu. The research was conducted in January to March 2015 with two study cycles consisting of: (1) the first cycle, and (2) the second cycle which includes the following activities: planning, action, observation, and reflection. Results of the study as follows: (1) an increase in the quality of learning through the implementation of a combination of lectures, demonstrations and exercises with contextual learning approach given by the teacher, starting from the first cycle to the second cycle, and (2) the application of a combination of lectures, demonstrations and exercise with contextual learning approach to students in the first cycle reaches an average value of 62.9 and the second cycle reached an average of 87.1. Of the 14 students who took the test individually formative there are 9 people who were able to cross the line to pass a minimum in the first cycle and all the students pass the study on the second cycle. Thus, learning by applying a combination of lectures, demonstrations and exercises with contextual learning approach to student mastery of the material in relation to the learning of mathematics to be taught basic competencies was able to achieve study defined indicators.